Prevalence of asymptomatic ST segment elevation in right precordial leads with right bundle branch block (Brugada-type ST shift) among the general Japanese population. Issue 2 (1st August 2001) - Furuhashi, M; Uno, K; Tsuchihashi, K; Nagahara, D; Hyakukoku, M; Ohtomo, T; Satoh, S; Nishimiya, T; Shimamoto, K
Abstract : OBJECTIVE: To examine the modality and morbidity of asymptomatic ST segment elevation in leads V1 to V3 with right bundle branch block (Brugada-type ST shift). METHODS: 8612 Japanese subjects (5987 men and 2625 women, mean age 49.2 years) who underwent a health check up in 1997 were investigated. Those with Brugada-type ST shift underwent the following further examinations over a two year period after the initial check up: ECG, echocardiogram, 24 hour Holter monitoring, treadmill exercise testing, signal averaged ECG, and slow kinetic sodium channel blocker loading test (cibenzoline, 1.4 mg/kg). RESULTS: Asymptomatic Brugada-type ST shift was found in 12 of 8612 (0.14%) subjects. Eleven of these 12 subjects were followed up. Follow up ECG exhibited persistent Brugada-type ST shift in seven of 11 (63.6%) subjects. ST shift was transformed from a saddle back to a coved type in three subjects. None of the subjects had morphological abnormalities or abnormal tachyarrhythmias. Positive late potentials were found in seven of 11 (63.6%) subjects. Augmentation of ST shift was shown by both submaximal exercise and drug administration in one of the 11 subjects (9.1%). CONCLUSIONS: Asymptomatic subjects with Brugada-type ST shift were not unusual, at a rate of 0.14% in the general Japanese population. Almost all of the subjects had some abnormalities in non-invasive secondary examinations. Additional and prospective studies are needed to confirm the clinical significance and the prognosis of asymptomatic Brugada-type ST shift.